IDENTITY AND ALIENATION IN FRANZ KAFKA’S THE METAMORPHOSIS - Iqra Manzar; Saman Musawar; Muhammad Fayaz (International Journal of Contemporary Issues in Social Sciences, 2024)
This research is designed to explore Franz Kafka’s novel “The Metamorphosis” to analyze the general motifs of Gregor Samsa’s role as the embodiment of alienation and the confusion of his identity. Thus, by scrutinizing Gregor’s Change into an insect and its effects, the study reveals how Kafka responds to oppressive forces of society as well as families that, in turn, deform people’s character and cause inner turmoil. Through the analysis of the life of Gregor Samsa as a person who desperately fights for his identity and his family that eventually rejects him, this paper identifies the vicious circle of identity loss and identity alienation. The existential, psychoanalytic, and sociocultural theories help a reader or audience to get a broader view of these concepts. How Kafka depicts the condition of Gregor is relevant to the modern debates on psychology, self-estimation and alienation of the individual. This paper adds valuable insights into Kafka’s technique of telling a story and themes of his most enigmatic short work, ‘The Metamorphosis,’ reaffirming its significance to contemporary literary and cultural analysis.